Phenomenology Study of Teachers’ Satisfaction at the State Junior High School - Pramono, Rudy; Amalia, Siti (Universitas Islam Negeri Raden Intan Lampung, 2020)
Teacher is one of several professions that is quite popular in Indonesia. Like many other profession, many factors are involved to determine the success of a teacher, one of which is job satisfaction. This study was aimed to provide information about the teachers' job satisfaction at the State Junior High School. The phenomenology approach was used to explore the teachers’ experience. The data were obtained from interviews and observations on the teachers. All primary and secondary data from the results of interviews and observations were collected and analyzed through four stages of analysis (analysis, horizontalization, meaning classification, and essence description). The subjects of this study were 15 main respondents and 2 supporting of one of state junior high school in Bogor. This study reveals that teachers’ job satisfaction was based on peers, altruism, and work enjoyment. Besides, it was found that worship, merit, and reward were some of the essences obtained from the teachers’ job satisfaction. The researchers assumed that these phenomena contained the essence of a sense of religiosity. This study recommends the whole stakeholders to pay more attention on the teachers' job satisfaction to supoort the learning success at schools.